The Role of Social Media in Improving Tax Compliance in the Theory of Planned Behavior - Zikrulloh Zikrulloh (Ikatan Sarjana Komunikasi Indonesia, 2023)
The government always strives to improve tax compliance to achieve the target of state revenues. In practice, the government has initiated the use of social media as a communication medium to disseminate information, education, and interaction to the broader citizens. This study aims to determine the role of social media in improving individual tax compliance using the Theory of Planned Behavior (TPB) approach. The data collection technique was carried out using an online survey method with a questionnaire instrument. The data analysis was conducted using the Structural Equation Modeling (SEM) Model to test the relationship between variables in a model. The study results show that the attitude variable on taxpayers intention has a p-value = 0.064 > 0.05 with a coefficient of -15.7%. In line with the attitude variable, the subjective norms variable has a p-value = 0.670>0.05 with a coefficient of 3.1%. On the other hand, the perceived behavioral control has a coefficient of 20.1% (with p-value <0.05), the tax moral obligation variable has a p-value = 0.000 < 0.05 with beta = 28.7%, and the use of social media also has p-value < 0.05, with a coefficient of 39.4%. The use of social media positively and significantly influences the individual taxpayers’ intention to behave in tax compliance. Adding social media variables to the study also broadens the implementation of TPB theory from a communication studies perspective, and gives recommendations to the government to improve the quality of information content appropriately through social media.